DB1000N SOFTWARE AS UKRAINE’S MILITARY UTILITY TO COUNTER RUSSIAN INVASION IN 2022 - Anshori, Muhammad Fikry (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2022)
As Russia launched an invasion in every domain of warfare, including cyberspace, Ukraine employed an Information Technology (IT) army equipped with software called db1000n on March 2022. This article seeks to explain how the use of db1000n helps Ukraine against the 2022 Russian invasion. Using a case study as the research method and Susan Martin's military utility concept as the analytical framework, this article found that db1000n helps to support Ukraine's cyber warfare effort by being Distributed Denial of Service (DDoS) attack software that possesses three types of military utility, namely technical utility, tactical utility, and strategic utility. Nevertheless, db1000n still has some limitations that cannot secure an easy victory in cyber warfare. Â